Implementation of Positive Cultural Planning as a Strategy to Achieve the Effectiveness of Kalirejo 02 State Elementary School - Dyah Ayu Permatasari; AY Soegeng Ysh; Ngurah Ayu Nyoman Murniati (Journal of Educational Sciences, 2026)
This study aims to analyze and describe the implementation of positive culture planning as a strategy to achieve school effectiveness at Kalirejo 02 State Elementary School. The research method used is qualitative, with data collection through interviews, observations, and document reviews. The results of the study indicate that the implementation of positive culture has been implemented effectively through a comprehensive management process. Planning is carried out strategically by integrating the values of the Pancasila Student Profile into the School Vision and formal programs outlined in the RKS/RKAS. Implementation is focused on the application of Positive Discipline, characterized by the consistent use of Class Beliefs and the Restitution Triangle method by teachers. This implementation has had a significant impact on school effectiveness, as evidenced by: a significant decrease in student violation cases, an increase in the quality of a safe and supportive school climate, and an increase in teacher job satisfaction. However, challenges faced are maintaining consistent implementation across all staff and optimizing parental involvement to strengthen a positive culture at home. Overall, a positive culture at Kalirejo 02 State Elementary School serves as a successful management strategy that improves students' internal discipline and creates a holistic learning ecosystem.